The challenge of career guidance and counseling during the covid-19 pandemic - Suwidagdho, Dhanang; Dewi, Suci Prasila (Universitas Islam Negeri Raden Intan Lampung, 2020)
The Covid-19 pandemic has also opened up opportunities on how career guidance services build roles in the wider community. Whereas in the world of work, globally everything has stopped, projects have been postponed, and workplaces have been closed indefinitely. This journal is a literature review that discusses career guidance and counseling services that are very important in an effort to help victims of layoffs that have occurred as well as workers in general. This problem can be solved through the career guidance function as a treatment to help individuals overcome career-related problems. The essence of the function of career guidance as a stimulus is the ability to anticipate all future possibilities and achieve career maturity. In the future, workers mindsets need to be changed through career guidance services in the form of knowledge assistance on how to manage finances. Through providing career guidance services as a form of treatment and stimulus, individuals will have self-motivation to rise from adversity and get new jobs that match their interests and expertise, find another source of income and to build passive income.